2006
DOI: 10.1074/jbc.m512063200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Interactions between FXYD Proteins and Na+,K+-ATPase

Abstract: Interactions of rat FXYD4 (corticosteroid hormone-induced factor (CHIF)), FXYD2 (␥), or FXYD1 (phospholemman (PLM))

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Molecular and biochemical studies indicate that PLM and other FXYD proteins interact with TM2 and TM9 of Na + -K + -ATPase (31,45). Molecular modeling suggests that PLM docks into the groove between TM2, TM6 and TM9 of Na + -K + -ATPase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular and biochemical studies indicate that PLM and other FXYD proteins interact with TM2 and TM9 of Na + -K + -ATPase (31,45). Molecular modeling suggests that PLM docks into the groove between TM2, TM6 and TM9 of Na + -K + -ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the TM domain of PLM interacts with the TM domains of Na + -K + -ATPase (31). It is therefore of interest to determine if the TM domain of PLM is necessary for its interaction with NCX1.…”
Section: Association Of Ncx1 With Plm Requires the Cytoplasmic Domainmentioning
confidence: 99%
“…The Na ϩ /K ϩ -ATPase consists of a catalytic ␣-subunit with 10 transmembrane segments and a ␤-subunit involved in membrane insertion and as a modulator of transport properties (5). In particular, cross-linking and modeling studies revealed the direct interaction between the Na ϩ /K ϩ -ATPase ␣-subunit and members of the FXYD family (␥ and CHIF), which involves the binding of a single transmembrane domain into a groove formed by M2, M6, and M9 transmembrane helices of the Na ϩ /K ϩ -ATPase (6,7). PLM appears to be a major control point in the function of heart cells, although its specific physiological role is unclear, complicated by the possibility that its regulatory effect on the Na ϩ /K ϩ -ATPase may depend on the phosphorylation state of PLM (8) as well as other less well established functional roles (e.g.…”
Section: Human Phospholemman (Plm)mentioning
confidence: 99%
“…In some experiments cells were maintained in a K ϩ -free RPMI 1640 medium (Biological Industries). Rat ␣1-Na ϩ /K ϩ -ATPase-expressing cell clones were produced by transfecting the above YFP-␣1 cells with rat ␣1 tagged in its N terminus by the hemagglutinin A (HA) epitope subcloned into pcDNA-3 (21). Transfected cells were cultivated in the presence of 10 M ouabain, and stably transfected ouabain-resistant cell clones were isolated.…”
Section: Methodsmentioning
confidence: 99%